Sleep hygiene linked to patient-reported outcomes & objective sleep measures prior to upper extremity orthopaedic surgery - Giordano, Nicholas A.; Getz, Tatiana; Gottschalk, Michael; Miller, Andrew H.; Dupree Jones, Kim; Park, Jasmine; Zhu, Yining; Gong, Annabelle; Hudson, Jack; Selimovic, Selma; Taub, Sarah M.; Klosky, Amanda K.; et al. (Frontiers in Pain Research, 2025)
BackgroundSleep hygiene is a modifiable factor that influences sleep quality, which is vital to the body's healing process and pain response. However, poor sleep hygiene, characterized by irregular sleep schedules, inappropriate sleep environments, or the use of stimulants before bedtime, can exacerbate sleep disturbances and impairment, thus diminishing sleep quality, exacerbating pain hypersensitivity, and protracting postoperative recovery. Despite being modifiable, sleep hygiene is rarely assessed preoperatively and may be a driver of the relationship between poor sleep quality and pain response in surgical patient populations. Furthermore, there is a dearth of research examining the relationship between sleep hygiene and objective sleep measures in an ambulatory surgical patient population.PurposeThis analysis examined the association between sleep hygiene habits and both pain and sleep quality in a sample of patients undergoing orthopaedic surgery utilizing patient-reported outcomes and objective longitudinal measures of sleep quality, known as actigraphy.MethodsParticipants undergoing orthopaedic surgery on their upper extremity at a large urban academic medical center in the Southeastern United States were recruited, consented, and enrolled in this study approximately 2 weeks before surgery between March 2022 and April 2023. Participants completed a series of surveys assessing their sleep hygiene, sleep quality, and pain interference preoperatively. For example, participants completed the Sleep Hygiene Index and the Patient-Reported Outcome Measurement Information System (PROMIS) Pain Interference measure. In addition, participants wore an actigraphy device on the wrist of their non-surgical extremity, which measured sleep efficiency and total sleep time in the days prior to surgery. Linear regressions examined the association between preoperative sleep hygiene scores and pain interference, sleep efficiency, and total sleep time.ResultsThis sample included 30 participants. The average Sleep Hygiene Index score was 10.87 (±6.71) and the sample's average PROMIS Pain Interference T-score was 63.73 (±9.59). Actigraphy derived total sleep time per day was 362.97 (±154.02) minutes and an average sleep efficiency score of 91.98 (±3.72). Regression models showed that poorer sleep hygiene (e.g., higher scores) was associated with worse PROMIS Pain Interference T-scores (95% CI: 0.14, 1.04; p = .04). In addition, participants with worse sleep hygiene scores had worse sleep efficiency (β = −0.21; 95% CI: −0.41, −0.014; p = .037) and had fewer minutes in their total sleep time (β = −8.91; 95% CI: −17.10, −0.72; p = .034).ConclusionThis analysis indicates that poorer sleep hygiene is associated with both increased pain interference and poorer sleep quality among patients about to undergo orthopaedic surgery on their upper extremity. These findings highlight the need to assess and educate patients on proper sleep hygiene prior to surgery in an effort to help foster high-quality restorative sleep that promotes postoperative recovery. This study is among the first to examine the possible contributions of sleep hygiene, a modifiable factor, on both patient-reported outcomes and objective measures of sleep over a prolonged period among patients undergoing orthopaedic surgery in an ambulatory setting.